KEPATUHAN NIGERIA TERHADAP YAOUNDÉ CODE OF CONDUCT DALAM KASUS PEMBAJAKAN DAN PEROMPAKAN BERSENJATA NEGARA NIGERIA DI TELUK GUINEA TAHUN 2016-2021 - Jessika Ami Arifin, (2023)
Piracy is a global phenomenon that has a negative impact on the security of all global maritime traffic. Incidents of piracy and armed robbery increased in 2015 and will not decrease until 2021. There are three geographical areas of concern: piracy in Southeast Asia, especially the Strait of Malacca and the South China Sea, which has been considered problematic since the 1990s; the Somali Coast and the Horn of Africa, which has received high attention since 2007; and piracy in West Africa, especially the Gulf of Guinea, which has been recognized as the third most threatened area since 2011. Several piracy incidents in recent months, particularly the kidnapping of seafarers have highlighted the threat to commercial shipping lanes in the Gulf of Guinea. According to the latest global piracy report published by the International Maritime Bureau (IMB), 38 piracy incidents have been recorded since the beginning of 2021. In the first three months of 2021, the IMB (International Maritime Bureau) Piracy Reporting Center reported 33 vessels boarded, 2 attempted assaults on crew and crew, 2 vessels shot at, and I vessel hijacked. The Gulf of Guinea continues to be a very dangerous region for seafarers with 43% of all reported piracy incidents occurring in the region. Attacks in the region are reportedly becoming more violent with larger groups of seafarers being kidnapped. Despite the rising tide of piracy in the Gulf of Guinea, many countries in the region, particularly Angola, Equatorial Guinea and the Democratic Republic of Congo have largely ignored the issue. These countries instead focus on inter-state issues on land and ignore serious maritime security issues. Combined with the poor socio-economic conditions in these countries, the lack of foresight on piracy encourages individuals with limited economic opportunities to turn to maritime crime, providing an opportunity for an increased link between sea piracy and regional crime. This paper uses qualitative research techniques by demonstrating the maritime security situation in western Africa, especially the Gulf of Guinea, supported by statistical analysis of piracy incidents from 2015-2021 to discuss the causes and regional efforts to address the problem. This paper will also present several recommendations aimed at enhancing maritime security to eradicate the threat of piracy in the region.